The Development of Digital Teaching Materials on The Topic of Sound Waves to Practice Problem Solving Skills - Rahmida Yolanda; Abdul Salam M; Dewi Dewantara (Universitas Tidar, 2024)
The low ability of students in problem solving and teaching materials that are still lacking for students to be able to make learning resources, especially learning from home. In general, this study aims to describe the feasibility of digital teaching materials on sound wave materials developed to practice ; problem solving skills. In particular, this study aims to describe; (1) The validity of digital teaching materials, (2) The practicality of digital teaching materials, and (3) The effectiveness of digital teaching materials. By developing digital teaching materials in the form of teaching materials, lesson plans, student worksheet, and study result test. The research was developed using the ADDIE model. The test subjects were 14 students of class XI MIPA 1 SMA Negeri 10 Banjarmasin. The sampling technique was carried out based on consistency in the pre-test, post-test, and attendance. The research data were obtained from validation test sheets, learning outcomes tests, and student response questionnaires. The data were analyzed descriptively-qualitatively, the average, and the minimum completeness criteria. The results showed that; (1) The validity of teaching materials with an average score of 3.63 is in the very good category, (2) the practicality of teaching materials with an average of 3.24 gets a good category, and (3) the effectiveness of teaching materials using the Minimum Completeness Criteria declared effective with 86% of students having a minimum completeness criteria score and an N-gain of 0.71 so that digital teaching materials can be said to be good. The conclusions of the research obtained are the development of digital teaching materials on Sound Wave material to practice problem solving skills which are declared suitable for use in learning activities. With the existence of digital teaching materials, sound waves can be a decent source of learning for students and practice problem solving skills